2016
DOI: 10.1186/s40795-016-0074-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of the effects of a prudent diet on cardiovascular risk factors, gene expression, and DNA methylation - the Diet and Genetic Intervention (DIGEST) Pilot study

Abstract: Background: Risk of cardiovascular disease (CVD) can be increased by single-nucleotide polymorphisms (SNPs) in the 9p21 region of the genome. However, observational studies have shown that the deleterious effect of 9p21 SNPs on CVD might be offset by consuming a diet rich in fresh fruits and vegetables. This association may be driven by diet-influenced modifications in epigenetic and gene expression profiles. In this pilot study, we aimed to: i. test the feasibility of provision of a 'Prudent' and 'Western' di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Major changes in self-reported dietary patterns among DIGEST participants were evident after 207 2 weeks as summarized in Table 1. Although there were no significant changes in BMI or average 208 caloric intake between the two treatment arms, greater palatability and satiety was previously 209 reported for participants assigned to a Prudent diet [25]. As expected, the Prudent diet group (W-P) 210 had higher intake of dietary fiber (total, insoluble, soluble), major electrolytes (K, Mg) fruit and/or 211 vegetable, vitamins, poly:sat, protein, and sugar or total carbohydrates, whereas the P-W group had 212 higher intake of fat (total, saturated, and trans), sodium and cholesterol.…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…Major changes in self-reported dietary patterns among DIGEST participants were evident after 207 2 weeks as summarized in Table 1. Although there were no significant changes in BMI or average 208 caloric intake between the two treatment arms, greater palatability and satiety was previously 209 reported for participants assigned to a Prudent diet [25]. As expected, the Prudent diet group (W-P) 210 had higher intake of dietary fiber (total, insoluble, soluble), major electrolytes (K, Mg) fruit and/or 211 vegetable, vitamins, poly:sat, protein, and sugar or total carbohydrates, whereas the P-W group had 212 higher intake of fat (total, saturated, and trans), sodium and cholesterol.…”
mentioning
confidence: 79%
“…Since all DIGEST participants had poor Prudent diet eating habits at baseline (Table 1), we hypothesized that assigning a Prudent diet (W-P) from food provisions would likely induce a more pronounced metabolic phenotype change than a Western diet (P-W); indeed, several top-ranked metabolites (q < 0.05, FDR) measured in plasma and urine were largely positively associated with a Prudent diet as shown in volcano plots ( Figure S5). Unlike controlled feeding studies within a laboratory setting, DIGEST participants were provided cooking suggestions with meal plans by a dietician that still allowed for flexibility in food preparations [25]. In this study, short-term dietary changes were found to impact the intake of 20 specific nutrient categories from self-reported diet records ( Table 2; Table S1; Figure S4).…”
Section: Contrasting Diets From Food Provisionsmentioning
confidence: 98%
See 3 more Smart Citations